Hurma suyu üretim teknolojosinin geliştirilmesi - Güven, Yasemin (My University, 2005)
The date (Phoenix dactylifera L.) is the oldest agricultural crop which has been known to becultivated by man kind. It is a widely grown fruit especially in semiarid regions of the MiddleEast countries and has been an important part in the economic and social lives of the people ofthese regions. The date, also named as "Life tree", has been farmed in the area of approximately800.000 hectares and more than 2000 different cultivars of date palm are known to exist all overthe world.In this research, concentrate of the date syrup has been made on a laboratory scale by the processconsisting of extraction, pressing, clarification, filtration and concentration. The sugar content ofthe date is quite high but on the other hand fat and protein content is very low. The fatty acidcomposition includes of saturated and mono-unsaturated fatty acids. Although the protein rate ofdate is quite low, in comparison with the other dried fruits this rate and the number of the aminoacid types are high. Additionally date fruit is a highly nutritious food product, rich in energy andmany vitamins and minerals. Taking into consideration of these nutritional properties, it can beforeseen that the syrup, which will be produced from a date will be a healthy product andmeanwhile it is an innovative product in the fruit juice industry in Turkey. Based on thesepurposes this research has been made.In this research, effective parameters such as mash enzyme treatment, increasing the yield of themash enzyme, increasing the time of the extraction period on the date extraction were definedand observed. It is found that addition of the mash enzyme solution increases the yield ofextraction (23%). The date, 500 g without pits, was mixed with date water ratios (1:3) andextracted at 50ºC, 1,5 hours. The necessary enzyme quantity, which should be added to thissolution is calculated as 6 ml Fruktozym MA (5%). It is found that increasing of this quantity withthe rate of 30% does not have any effect on the yield of the extraction. Likewise increasing of thetime of extraction has the same notr effect. The necessary quantities of clarification enzyme andclarification agent were calculated during the clarification just after the pressing period. At thefinal stage the date concentrate was obtained and analyzed for the acidity, pH, sugar, organic acidand mineral contents.In conclusion, the date syrup was found to be a good source of sugar, potassium, magnesium andcalcium. The juice which will be produced from the date concentrate has a fresh taste and highlynutritious as well.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2005
Keywords: Hurma meyvesi; Meyve suyu konsantresi üretimi; Date fruits; Date palm; Date syrup; Phoenix dactylifera; Extraction